A study of the comparative effect of cerium oxide and cerium peroxide on stimulation of angiogenesis: Design and synthesis of pro‐angiogenic chitosan/collagen hydrogels. Issue 12 (7th July 2022) - Zubairi, Waliya; Tehseen, Saimoon; Nasir, Muhammad; Anwar Chaudhry, Aqif; Ur Rehman, Ihtesham; Yar, Muhammad
Abstract: Poor angiogenesis at injury site is a major problem in chronic wounds, which could lead to limbs amputation in adverse cases. To overcome this issue, several efforts have made in literature and by our group as well to develop pro‐angiogenic agents. For this purpose, metal oxides due to their oxidative potential have been studied and found very attractive agents. Cerium oxides are proven to be non‐toxic and their biological studies have already proved their importance in preventing chronic inflammation, and neurological diseases among several others by modulating the intracellular reactive oxygen species. In current study, we report the synthesis and neovascularization activity of cerium oxide and cerium peroxide nanoparticles when loaded into chitosan and collagen hydrogel. The hydrogels were characterized by FTIR, SEM and XRD. The pro‐angiogenic behavior of these hydrogels was studied by in‐vivo CAM assay. It was found that cerium peroxide loaded material showed significantly increase in angiogenesis as compared to cerium oxide loaded materials. It was demonstrated that cerium peroxide hydrogels enhanced the angiogenic capability in CAM assay as compared to cerium oxide and hence holds good potential for chronic ulcer and burn wounds healing. Abstract :